Can ACE2 Receptor Polymorphism Predict Species Susceptibility to SARS-CoV-2? - Devaux, Christian A.; Pinault, Lucile; Osman, Ikram Omar; Raoult, Didier (Frontiers in Public Health, 2021)
A novel severe acute respiratory syndrome coronavirus, SARS-CoV-2, emerged in China in December 2019 and spread worldwide, causing more than 1.3 million deaths in 11 months. Similar to the human SARS-CoV, SARS-CoV-2 shares strong sequence homologies with a sarbecovirus circulating in Rhinolophus affinis bats. Because bats are expected to be able to transmit their coronaviruses to intermediate animal hosts that in turn are a source of viruses able to cross species barriers and infect humans (so-called spillover model), the identification of an intermediate animal reservoir was the subject of intense researches. It was claimed that a reptile (Ophiophagus hannah) was the intermediate host. This hypothesis was quickly ruled out and replaced by the pangolin (Manis javanica) hypothesis. Yet, pangolin was also recently exonerated from SARS-CoV-2 transmission to humans, leaving other animal species as presumed guilty. Guided by the spillover model, several laboratories investigated in silico the species polymorphism of the angiotensin I converting enzyme 2 (ACE2) to find the best fits with the SARS-CoV-2 spike receptor-binding site. Following the same strategy, we used multi-sequence alignment, 3-D structure analysis, and electrostatic potential surface generation of ACE2 variants to predict their binding capacity to SARS-CoV-2. We report evidence that such simple in silico investigation is a powerful tool to quickly screen which species are potentially susceptible to SARS-CoV-2. However, possible receptor binding does not necessarily lead to successful replication in host. Therefore, we also discuss here the limitations of these in silico approaches in our quest on the origins of COVID-19 pandemic.